Policy Implementation Gaps In Nigerian Local Governments: Causes And Remedies For Improved Governance - Okotie William; Anthony Mayowa Oladoyin (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2026)
Local governments in Nigeria are strategically placed in the constitution to spearhead development at the grassroots level, but the inability to bridge the gap between policy making and real implementation has remained the bane of good governance and service delivery to people. The paper analyses the nature, causes and impacts of policy execution deficits in the local government in Nigeria with specific reference to institutional capacity, fiscal and intergovernmental limitations, political interference, lack of accountability and low citizen involvement. Within the theoretical insights, the paper relies on the perspectives that are relevant, such as the theory of street-level bureaucracy and implementation theory, in order to examine how administrative practices and frontline discretion influence the results of the policy at the local level. Nigeria's local governments experience empirical data that is supported by comparative data of other African nations depicts implementation failures to be more structural rather than exceptional with roots in the weak governance systems, insufficient resources, and poor cross-governmental coordination. The research finds that the policy implementation gaps can be reduced by enhancing the institutional capacity, increasing its fiscal autonomy, enhancing transparency and accountability mechanisms, and by better engaging the community. These discoveries will help in unending discussions on local governance reform and provide policy-relevant information to enhance implementation effectiveness and service delivery in Nigeria.